An integrated approach for sustainable supply chain planning. (February 2015) - Boukherroub, Tasseda; Ruiz, Angel; Guinet, Alain; Fondrevelle, Julien
Abstract: This paper proposes an integrated approach for transposing sustainable development principles to supply chain planning models. Inspired by research on performance measurement, we designed a method that links sustainability performance to supply chain decisions, and allows setting coherent performance measures. By transposing this method to a multi-objective mathematical programming, the supply chain planning is optimized while the economic, environmental and social performances are all coherently integrated into the model. To illustrate our approach, we applied it to a Canadian lumber industry case. We solved the mathematical model by using the weighted goal programming technique, which results in a set of "compromise" solutions allowing the decision maker to choose the alternative that reflects the balance he/she wishes to make regarding the three dimensions of sustainability.